UPAYA MENINGKATKAN MOTIVASI BELAJAR QUR’AN HADIT MELALUI MODEL PEMBELAJARAN TWO STAY TWO STRAY - supardi supardi; Sugiati (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This study aims to analyze learning activities and increasing motivation to study Al-Qur’an hadith using the two stay two stray learning model. The research method uses classroom action research. The research results found: First, pre-cycle student learning activities have a low activity level, the first cycle of moderate activity levels, and the second cycle of high activity levels. An increase of 25%, from pre-cycle to first cycle. And 26% from the first cycle to the second cycle. Second, the pre-cycle learning motivation is low, the first cycle is medium, and the second cycle is high. Increased motivation 22% from pre cycle to the first cycle and 20% from the first cycle to the second cycle. The two stay two stray learning model can increase students' motivation to learn the Qur'an hadith. The more effective learning of the Qur'an and hadith using the two stay two stray learning model, the higher the student's learning motivation, the higher the student's learning motivation.